Comparison of Dual-Energy Computed Tomography Pulmonary Angiography-Derived Contrast Enhancement with Standard Dual-Energy Pulmonary Angiography in Diagnosing Subsegmental Pulmonary Embolism: A Prospective Study - Yadav, Vivek; Singhal, Manphool; Maralakunte, Muniraju; Sharma, Navneet; Sharma, Arun; Lal, Anupam (Indian Journal of Radiology and Imaging, 2023)
Objective In this study, we compare the diagnostic accuracy of dual-energy (DE) computed tomography pulmonary angiography (CTPA) derived contrast enhancement (DECTPA, CTPA images with iodine maps) with standard dual-energy pulmonary angiography (SCTPA) for diagnosis of subsegmental pulmonary embolism in the cases with clinical suspicion of acute pulmonary embolism (APE).Materials and Methods We included 50 cases with clinical suspicion of APE that were referred for CTPA. All the patients underwent CTPA in the dual-energy protocol. Two radiologists evaluated the images. The first radiologist interpreted the SCTPA images (vascular images) and the second radiologist interpreted the DECTPA (CTPA images with iodine maps) for findings of APE. We calculated the sensitivity, specificity, and negative predictive value of DECTPA vis-à-vis SCTPA images.Results The DECTPA with the advantage of iodine map utilization yielded higher detection of thrombi in peripheral subsegmental arteries (72 vs. 99; p = – 0.001) as compared to the SCTPA images by identification of 18 new perfusion defects (interquartile range [IQR]: 0–1) that were consistent with APE. Filling defects were identified in 27 (IQR: 0–4) more subsegmental arteries supplying these 18 areas, which were not detected on SCTPA alone. These 18 perfusion defects were identified in 13 cases. In these 13 cases, 4 new cases were diagnosed that were negative on CTPA (p = –0.125).In the evaluation of the APE, sensitivity and specificity were calculated and it was found that DECTPA showed 100% sensitivity and 86% specificity with 100% negative predictive value in the detection of thrombi as compared to the routine CTPA.Conclusion DECTPA has higher sensitivity and negative predictive value in the detection of the subsegmental perfusion defect identification as compared to SCTPA.
Keywords: acute pulmonary embolism; CT pulmonary angiography; dual-energy CT; iodine maps; subsegmental pulmonary thromboembolism